Risk and protective factors for childhood asthma: what Is the evidence? (2020)
To summarize the principal findings on risk and protective factors for childhood asthma, we retrieved systematic reviews on these topics in children (aged 1 to 18 years), up to January 2016, through MEDLINE, EMBASE, CINAHL, SCOPUS, and CDSR. A total of 227 studies were searched from databases. Among those, 41 systematic reviews (SRs) were included: 9 focused on prenatal factors, 5 on perinatal factors, and 27 on postnatal factors. Of these 41 SRs, 83% had good methodological quality, as determined by the Assess Systematic Reviews tool. After reviewing all evidence, parental asthma, prenatal environmental tobacco smoke, and prematurity (particularly very preterm birth) are well-established risk factors for childhood asthma. Current findings do suggest mild-to-moderate causal effects of certain modifiable behaviors or exposures during pregnancy (maternal weight gain or obesity, maternal use of antibiotics or paracetamol, and maternal stress), the perinatal period (birth by Caesarean delivery), or postnatal life (severe respiratory syncytial virus infection, overweight or obesity, indoor exposure to mold or fungi, and outdoor air pollution) on childhood asthma, but this suggestive evidence must be confirmed in interventional studies or (if interventions are not feasible) well-designed prospective studies.